Energy, exergy, and environmental analysis for energy intensive industrial equipment in Malaysia / Md. Hasanuzzaman - Md. Hasanuzzaman, - (2011)
Worldwide, industrial sector accounts for about 35% of the total energy used. In Malaysia, 48% of total energy is used in this sector. Boilers, furnaces and electric motors are the energy intensive equipment of almost every industry and consume a significant amount of energy. The aim of the thesis is analyze the utilization of energy and exergy, energy saving and emission reduction for the energy intensive industrial equipment. In this study, the useful concept of energy and exergy is analyzed to investigate the energy and exergy efficiencies, energy and exergy losses in boilers, furnaces, heat exchangers and economizer. Energy use, energy and bill savings, payback periods and emission reduction of different energy saving options (i.e. economizer, variable speed drive) for boilers, furnaces, and electric motors were analyzed and presented in this thesis. From the comparative analysis, it is found that the average energy efficiency of the boilers is 68.7%. It is also found that average exergy efficiency of the boilers is 22%. The average energy efficiency of furnaces found to be 30%. The average exergy efficiency of the furnaces has been calculated and found to be 19%. The major exergy destruction was found in the combustion chamber (55%) of the boilers and annealing chamber (62%) of the furnaces. Energy effectiveness of counter flow heat exchangers has been investigated and found to be 65% where the exergy effectiveness found to be 59%. By applying a heat recovery system, about 10% of the boilers and 30% of the furnaces energy can be saved with payback periods less than 1 year in the most cases. The energy effectiveness of economizer varied from 66% to 73%. Exergy effectiveness also calculated and found to be varied from 47% to 65%. It has been estimated that annually 67,868 MWh energy and 4,343,531 US$ bill can be saved by replacing standard motors with high efficiency motors. On the other hand, 51,510tons of CO2 385 tons of SO2 and 141 tons of NOx emission can be reduced against the aforementioned energy savings. By introducing variable speed drive in motor drive systems to match load requirements, energy savings estimated to be annually 542,941 MWh, 900,789 MWh and 1,098,222 MWh for 20%, 40% and 60% motor speed reduction, respectively. And corresponding annual bill savings found to 34,748,244 US$, 57,650,496 US$ and 70,286,221 US$, respectively. Emissions could be reduced by 836,831 tons of CO2, 6217 tons of SO2 and 2285 tons of NOx by motor speed reduction of 60%. By improving the power factor near unity, about 10% of energy can be saved in the Malaysian industrial sector. Based on the results, it is found that a sizable amount of energy can be saved by applying different energy savings measures and sizable amount of emissions can be reduced with reasonable payback periods.